"Beyond Their Actual Limits": Immersion, Interactivity, and the Virtual Sublime in Burke and Video Games. Issue 1 (January 2023) - Kim, Yaeri
This article examines the experience of the sublime engendered by video games and the function of immersion and interactivity in producing this effect. A close inspection of the history of the sublime as an aesthetic principle and related cultural practices reveals that the elements of immersion, interactivity, and virtuality were already integral to Burke's seminal conceptualization, as well as in architecture and visual media, before the emergence of digital media. The techniques and technologies of the immersive sublime deployed by preexisting spatial and visual art forms are inherited, revised, and enhanced in video games, as demonstrated by the analysis of the undersea exploration game ABZÛ . In this sense, the video game simultaneously marks the continuation of and new developments in the interlinked histories of the sublime and technology.